Film for film capacitor, metal laminate, film capacitor, power control unit, electric vehicle, and electric aircraft
Patent Information
- Application Number
- JP2024121997
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-31
- Filing Date
- 2024-07-29
- Publication Date
- 2025-02-13
AI Technical Summary
【0010】 本発明によれば、高い耐湿熱性とセルフヒーリング性を具備し、フィルムコンデンサの誘電体として使用したときの発熱、コート層の熱分解、および加水分解による性能低下を軽減できる、フィルムコンデンサ用フィルムを提供することができる。
Smart Images

Figure 2025021454000001 
Figure 2025021454000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a film for a film capacitor that can be suitably used as a dielectric, and to a metal laminate, a film capacitor, a power control unit, an electric automobile, and an electric aircraft that use the same. [Background technology]
[0002] In recent years, due to global environmental issues and other factors, the market has expanded for hybrid electric vehicles (HEVs) and plug-in hybrid electric vehicles (PHEVs), as well as electric motor-driven vehicles such as electric vehicles (EVs) and fuel cell vehicles (FCVs). As a result, the demand for film capacitors used in these vehicles has also increased rapidly.
[0003] Film capacitors are capacitors that use a resin film as a dielectric, and have excellent frequency characteristics and temperature stability. Examples of films used as dielectrics in film capacitors include polyester films such as polypropylene (PP) film, polyethylene terephthalate (PET) film, and polyethylene naphthalate (PEN) film, thermoplastic resin films such as polyphenylene sulfide (PPS) film, and polyetherimide (PEI) film, which is an amorphous thermoplastic resin film.
[0004] On the other hand, films with excellent heat resistance, such as polyetherimide film and polyphenylene sulfide film, generally have poor self-healing (SH) properties, and therefore have the drawback that the capacitance of a film capacitor that uses such a film as a dielectric decreases over long periods of use.
[0005] In response to this, a technology is known that improves the self-healing property by providing a coating layer on the base film, but the coating layer undergoes thermal decomposition or hydrolysis when exposed to high temperature and / or high humidity environments for a long period of time, and the film capacitor performance is not sufficiently maintained. In order to solve the above problems, a technology has been disclosed in which an antioxidant is incorporated into the coating layer (Patent Document 1). In addition, since polyetherimide films, polyethylene naphthalate films, etc. have a large dielectric loss tangent, when used as a film capacitor dielectric for an inverter smoothing capacitor, there is a risk that the film capacitor will generate a large amount of heat and the performance of the film capacitor will be reduced. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 9-141809 Summary of the Invention [Problem to be solved by the invention]
[0007] However, the conventional technology as shown in Patent Document 1 has a problem in that it is insufficient to simultaneously reduce thermal decomposition and hydrolysis of the coating layer under high temperature and / or high humidity environments and improve self-healing properties. In view of the background of the conventional technology, the present invention aims to provide a film for film capacitors that has high resistance to moist heat and self-healing properties and can reduce performance degradation due to heat generation and thermal decomposition and hydrolysis of the coating layer when used as a dielectric of a film capacitor. [Means for solving the problem]
[0008] The above-mentioned problems can be solved by the following invention. That is, the film for a film capacitor of the present invention is a film for a film capacitor having two types of resin layers with different thicknesses, in which, when the relatively thinner layer of the two types of resin layers is resin layer A and the relatively thicker layer is resin layer B, the film for a film capacitor has the resin layer A on at least one side of the resin layer B, and satisfies both of the following conditions 1 and 2. Condition 1: When the total amount of all the components of the resin layer A is taken as 100% by mass, the resin layer A contains 0.01% by mass or more and 10% by mass or less of an antioxidant. Condition 2: When the total amount of all the components of the resin layer A is taken as 100% by mass, the amount of the soluble portion of the resin layer A in any one of the following solvents a) to c) is 30% by mass or less. a) Methyl ethyl ketone b) Toluene c) Dioxane.
[0009] In addition, the film for a film capacitor of the present invention can also be made into the following embodiments, and can also be used to obtain a metal laminate, a film capacitor, a power control unit, an electric automobile, and an electric aircraft as described below. (1) A film for a film capacitor having two types of resin layers with different thicknesses, in which, of the two types of resin layers, the relatively thinner layer is resin layer A and the relatively thicker layer is resin layer B, the film for a film capacitor has the resin layer A on at least one side of the resin layer B, and satisfies both of the following conditions 1 and 2. Condition 1: When the total amount of all the components of the resin layer A is taken as 100% by mass, the resin layer A contains 0.01% by mass or more and 10% by mass or less of an antioxidant. Condition 2: When the total amount of all the components of the resin layer A is taken as 100% by mass, the amount of the soluble portion of the resin layer A in any one of the following solvents a) to c) is 30% by mass or less. a) Methyl ethyl ketone b) Toluene c) Dioxane (2) The film for film capacitors according to (1), having a melting point measured by DSC of 180°C or higher and 380°C or lower, and / or a glass transition temperature measured by DSC of 130°C or higher and 370°C or lower. (3) The film for a film capacitor according to (1) or (2), wherein the antioxidant includes a phenol-based antioxidant. (4) The film for a film capacitor according to any one of (1) to (3), wherein the resin layer A contains a carbodiimide. (5) The film for a film capacitor according to (4), wherein the content of the carbodiimide in the resin layer A is 0.01% by mass or more and 10% by mass or less, when the total amount of all components of the resin layer A is 100% by mass. (6) The film for film capacitors according to any one of (1) to (5), wherein the resin layer A has at least one structure selected from the group consisting of an ester bond, an ether bond, a carbonate bond, a urethane bond, a urea bond, an amide bond, an imide bond, an oxazoline ring, and an alkylene group. (7) The film for film capacitors according to any one of (1) to (6), wherein the resin layer A has a unit structure of at least one polymer selected from the group consisting of urethane acrylate polymers, acrylate polymers, urethane methacrylate polymers, methacrylate polymers, aliphatic polyethers, aliphatic polyesters, aliphatic polyamides, polyurethanes, polyureas, and epoxy resins. (8) The film for a film capacitor according to any one of (1) to (7), wherein the resin layer B contains at least one of the group consisting of polyarylene sulfide, polyethersulfone, polysulfone, polyimide, polyetheretherketone, and polyetherimide, and the total amount of the at least one is more than 50 mass% and not more than 100 mass%. (9) The film for a film capacitor according to any one of (1) to (8), containing, as the antioxidant, one that satisfies at least one of the following conditions A and B: Condition A: The melting point is higher than 155°C and lower than 400°C. Condition B: Solid at 155°C. (10) The film for a film capacitor according to any one of (1) to (9), wherein the resin layer A has a thickness of 1.0 nm or more and 1.0 μm or less. (11) The film for a film capacitor according to any one of (1) to (10), having a thickness of 0.1 μm or more and 10.0 μm or less. (12) A metal laminate having a metal layer on at least one surface of the film for a film capacitor according to any one of (1) to (11). (13) The metal laminate according to (12), comprising the resin layer B, the resin layer A, and the metal layer in this order. (14) A film capacitor using the metal laminate according to (13). (15) A power control unit having the film capacitor described in (14). (16) An electric vehicle having the power control unit described in (15). (17) An electric aircraft having the power control unit described in (15). Effect of the Invention
[0010] According to the present invention, it is possible to provide a film for film capacitors which has high moist heat resistance and self-healing properties, and which can reduce performance degradation due to heat generation, thermal decomposition of the coating layer, and hydrolysis when used as a dielectric in a film capacitor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The film for film capacitors of the present invention will be specifically described below. The film for film capacitors of the present invention is a film for film capacitors having two types of resin layers with different thicknesses, in which, when the relatively thinner layer of the two types of resin layers is resin layer A and the relatively thicker layer is resin layer B, the film for film capacitors has the resin layer A on at least one side of the resin layer B, and satisfies both of the following conditions 1 and 2. Condition 1: When the total amount of all the components of the resin layer A is taken as 100% by mass, the resin layer A contains 0.01% by mass or more and 10% by mass or less of an antioxidant. Condition 2: When the total amount of all the components of the resin layer A is taken as 100% by mass, the amount of the soluble portion of the resin layer A in any one of the following solvents a) to c) is 30% by mass or less. a) Methyl ethyl ketone b) Toluene c) Dioxane.
[0012] The film for film capacitors of the present invention has two types of resin layers with different thicknesses. Here, "different thicknesses" refers to a difference in thickness of 0.10 μm or more, and "two types of resin layers" refers to two resin layers with different compositions. A resin layer refers to a layer containing a resin as a main component, and a main component refers to a component contained in the layer at more than 50 mass% and not more than 100 mass% (hereinafter, the main component can be interpreted in the same way). Moreover, "different compositions" refers to a component constituting each layer being different from each other by 10 mass% or more and not more than 100 mass%, and preferably refers to a main component being different.
[0013] In the film for film capacitors of the present invention, when the thinner layer of the two resin layers is resin layer A and the thicker layer is resin layer B, the film for film capacitors has resin layer A on at least one side of resin layer B. In a film for film capacitors having such a configuration, resin layer B plays a role as a dielectric, and resin layer A plays a role of improving the self-healing property. That is, in the case of such a layer configuration, since resin layer A enhances the self-healing property of the film for film capacitors, a resin that is excellent in the properties required for a film for film capacitors such as heat resistance but has poor self-healing property can be used as the main component of resin layer B.
[0014] It is important that the film for a film capacitor of the present invention satisfies both of the following conditions 1 and 2 from the viewpoint of reducing short circuit breakdown when used as a dielectric of a film capacitor and from the viewpoint of enhancing self-healing properties. Condition 1: When the total amount of all the components of the resin layer A is taken as 100% by mass, the resin layer A contains 0.01% by mass or more and 10% by mass or less of an antioxidant. Condition 2: When the total amount of all the components of the resin layer A is taken as 100% by mass, the amount of the soluble portion of the resin layer A in any one of the following solvents a) to c) is 30% by mass or less. a) Methyl ethyl ketone b) Toluene c) Dioxane.
[0015] The film for film capacitors of the present invention satisfies both conditions 1 and 2, and thus when used as a dielectric for a film capacitor, the resin layer A is prevented from being thermally decomposed, hydrolyzed, or oxidized. Therefore, by using a film for film capacitors that satisfies both conditions 1 and 2 as a dielectric, the amount of capacitance reduction when the film capacitor is used at high temperatures for a long period of time can be suppressed. In other words, by adopting such an embodiment, the film capacitor can be made less susceptible to short circuit breakdown.
[0016] The antioxidant can reduce the deterioration of the resin layer A due to oxidation during high-temperature use, and therefore can enhance the self-healing property of the film capacitor when the film for film capacitor is used as a dielectric. However, if the antioxidant is added excessively to the resin layer A, the self-healing property of the film for film capacitor deteriorates and the capacitor capacity decreases during long-term use at high temperatures. In view of these points, from the viewpoint of enhancing the self-healing property of the film capacitor, the content of the antioxidant in the resin layer A is 0.01% by mass or more. On the other hand, from the viewpoint of enhancing the self-healing property and the effect of suppressing the decrease in the capacitor capacity during long-term use at high temperatures, the content of the antioxidant in the resin layer A is 10% by mass or less, preferably 5.0% by mass or less, and more preferably 0.9% by mass or less. Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and amine-based antioxidants. Among them, phenol-based antioxidants are preferred from the viewpoint of reducing the deterioration of the electrodes when used as a film capacitor.
[0017] In addition, in the film for film capacitors of the present invention, when the total components of the resin layer A are taken as 100 mass%, the soluble content of the resin layer A in any of the solvents a) to c) is 30 mass% or less, preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably less than 5.0 mass%. Here, the solvents a) to c) mean methyl ethyl ketone (hereinafter sometimes referred to as MEK), toluene, and dioxane, respectively. Methyl ethyl ketone is an organic solvent with moderate polarity, and is mainly used as a solvent for acrylates and methacrylates. Toluene is an organic solvent with low polarity, and is mainly used as a solvent for olefins. Dioxane is an organic solvent with high polarity, and is mainly used as a solvent for substances having a hydroxyl group. Thus, methyl ethyl ketone, toluene, and dioxane each easily dissolve different substances, and when the number of types of chemical bonds increases due to the formation of a crosslinked structure, the soluble content in multiple types of solvents decreases.
[0018] From the above viewpoints, the soluble content of resin layer A in these solvents is an index of the crosslink density of the molecular chains in resin layer A, and decreases as the crosslink density of the molecular chains increases. Normally, the effect of suppressing the decrease in the capacitance of a capacitor when used for a long period of time at high temperatures improves in proportion to the crosslink density of resin layer A, so the smaller the soluble content of resin layer A, the more preferable it is, and there is no particular lower limit, but from the viewpoint of feasibility, the lower limit is 0.01% by mass when the total components of resin layer A are 100% by mass.
[0019] The soluble content of the resin layer A can be measured by the following procedure. First, X (g) of the resin layer A is scraped off from the film for film capacitors and put into a specified solvent. Next, mixing is performed using a known vortex mixer, and the mixed solution is filtered through a filter to extract the filtrate. The extracted filtrate is then dried in an oven, and the mass Y (g) after drying is measured, and the soluble content of the resin layer A is calculated by the following formula. Details of the measurement method will be described later. Soluble content of resin layer A (%) = Y(g) × 100 / X(g).
[0020] The means for making the film for film capacitor of the present invention satisfy condition 2 is not particularly limited, but an example thereof includes a method of applying a coating composition containing components having multiple reactive sites onto a sheet to be the resin layer B, and crosslinking these components to form the resin layer A. Examples of methods for crosslinking these components include heating, and irradiation with ultraviolet rays or electron beams, and an appropriate method can be selected depending on the components contained in the coating composition.
[0021] When forming the resin layer A by coating, it is preferable to use a compound having two or more polymerizable functional groups as a component having a plurality of reaction sites in the resin layer A from the viewpoint of increasing productivity. Also, from the viewpoint of reducing the soluble content in each solvent, a compound having three or more polymerizable functional groups can be used. Examples of the polymerizable functional group include functional groups such as epoxy groups, vinyl groups, isocyanate groups, carboxyl groups, amino groups, and hydroxyl groups. Among them, vinyl groups are preferable from the viewpoint of suppressing deterioration of electrodes when used as a film capacitor, and also taking into consideration the stability of the coating liquid during processing. The polymerizable functional groups of the compounds may be the same or different.
[0022] The component having multiple reactive sites may be one type or a mixture of multiple types. Examples of such components include acrylates having two or more vinyl groups, urethane acrylates having two or more vinyl groups, epoxies having two or more epoxy groups, condensates of melamine and formaldehyde, mixtures of compounds having two or more isocyanate groups and compounds having three or more hydroxyl groups, and mixtures of compounds having two or more isocyanate groups and compounds having three or more amino groups. These components may also be used in appropriate combinations.
[0023] In the film for film capacitors of the present invention, from the viewpoint of enhancing the self-healing property, it is preferable that the resin layer A has at least one bond selected from the group consisting of ester, ether, carbonate, urethane, urea, amide, imide, oxazoline, and alkylene groups.
[0024] In the film for film capacitors of the present invention, from the viewpoint of enhancing the self-healing property, it is preferable that the resin layer A has a unit structure of at least one polymer selected from the group consisting of urethane acrylate polymer, acrylate polymer, urethane methacrylate polymer, methacrylate polymer, aliphatic polyether, aliphatic polyester, aliphatic polyamide, polyurethane, polyurea, and epoxy resin. The unit structure here refers to a structure (repeating unit) that is repeated two or more times in the molecular structure of the polymer.
[0025] In addition, in the film for film capacitors of the present invention, from the viewpoint of enhancing the self-healing property, it is preferable that the resin layer A has at least one structure selected from the group consisting of ester bonds, ether bonds, carbonate bonds, urethane bonds, urea bonds, amide bonds, imide bonds, oxazoline rings, and alkylene groups. Among them, when the resin layer A has urethane bonds or urea bonds, it becomes easier to control the crosslink density of the resin layer A, and it becomes easier to suppress the capacity decrease during long-term use. Therefore, it is more preferable that the resin layer A contains at least one compound selected from the group consisting of urethane acrylate polymers, urethane methacrylate polymers, polyurethanes, and polyureas, and it is even more preferable that the resin layer A contains at least one of urethane acrylate polymers and urethane methacrylate polymers in consideration of enhancing the moisture and heat resistance. In addition, even when the molecular chains of these components in the resin layer A form a crosslinked structure, it can be considered that the resin layer A contains these components.
[0026] The term "urethane acrylate polymer" refers to a compound obtained by polymerizing an acrylate containing a urethane bond, and the term "urethane methacrylate polymer" can be interpreted in the same way. The term "acrylate polymer" refers to a compound obtained by polymerizing an acrylate other than the urethane acrylate polymer, and the term "methacrylate polymer" can be interpreted in the same way. The terms "aliphatic polyether", "aliphatic polyester", and "aliphatic polyamide" refer to compounds having a structure in which aliphatic hydrocarbon groups are linked by ether bonds, ester bonds, and amide bonds, respectively. The term "polyurethane" refers to a polymer having a urethane bond other than the urethane acrylate polymer, and the term "polyurea" refers to a resin having a urea structure in the main chain. The term "epoxy resin" refers to a thermosetting resin that can be crosslinked by epoxy groups remaining in the polymer.
[0027] The resin layer A of the capacitor film of the present invention preferably has a unit structure of at least one polymer selected from the group consisting of urethane acrylate polymer, urethane methacrylate polymer, polyurethane, and polyurea. This makes it easier to improve the self-healing property. In addition, from the viewpoint of improving the moist heat resistance, it is more preferable that the resin layer A contains at least one of urethane acrylate polymer or urethane methacrylate polymer in an amount of 50% by mass to 100% by mass when the total mass of the resin layer A is taken as 100% by mass. These compounds may be used in mixture, or a copolymer of each unit structure may be used.
[0028] Of the raw materials for the resin layer A, from the viewpoint of promoting decomposition of the resin layer A upon insulation breakdown and enhancing the self-healing properties, it is more preferable to use an acrylate having two or more vinyl groups, a urethane acrylate having two or more vinyl groups, a mixture of a compound having two or more isocyanate groups and a compound having three or more hydroxyl groups, or a mixture of a compound having two or more isocyanate groups and a compound having three or more amino groups, and it is particularly preferable to use an acrylate having two or more vinyl groups, or a urethane acrylate having two or more vinyl groups.
[0029] In order to improve the resistance to moist heat and the reliability during long-term use at high temperatures, it is preferable to use a bifunctional or higher acrylate or a bifunctional or higher urethane acrylate as the raw material, and it is more preferable to use a trifunctional or higher acrylate or a trifunctional or higher urethane acrylate. The bifunctional or higher acrylate referred to here is an acrylate having two or more acryloyl groups in one molecule.
[0030] Specific examples of raw materials that can be used to form the resin layer A include "UV-3500BA" (manufactured by Mitsubishi Chemical Corporation), which is a butyl acetate diluted urethane acrylate, and "UN-3320HA" (manufactured by Negami Chemical Industrial Co., Ltd.), which is a hexafunctional urethane acrylate.
[0031] The film for film capacitors of the present invention preferably has a melting point measured by DSC of 180°C or more and 380°C or less, and / or a glass transition temperature measured by DSC of 130°C or more and 370°C or less. By using a film for film capacitors that satisfies at least one of the above conditions in a film capacitor, it is possible to reduce thermal shrinkage that occurs when used as a film capacitor. Hereinafter, the "melting point measured by DSC" and the "glass transition temperature measured by DSC" may be simply referred to as the "melting point" and the "glass transition temperature", respectively.
[0032] From the above viewpoints, the melting point of the film for a film capacitor is preferably 205° C. or higher, more preferably 215° C. or higher. On the other hand, from the viewpoint of moldability, the melting point of the film for a film capacitor is preferably 350° C. or lower.
[0033] From the above viewpoints, the glass transition temperature of the film for a film capacitor is preferably 150° C. or higher, more preferably 165° C. or higher, and further preferably 180° C. or higher. On the other hand, from the viewpoint of moldability, the glass transition temperature of the film for a film capacitor is preferably 350° C. or lower.
[0034] The melting point of the film for film capacitors can be measured by the following procedure. First, in accordance with JIS K-7122 (1987), the film for film capacitors is heated from 25°C to 350°C (380°C if the melting peak cannot be observed) at a heating rate of 20°C / min to obtain a differential scanning calorimetry chart. Next, the melting peak temperatures are obtained from the differential scanning calorimetry chart based on the method described in JIS K-7121 (1987), and the highest melting peak temperature among them is taken as the melting point. The measurement method will be described in detail later.
[0035] The glass transition temperature of the film for film capacitors can be measured by the following procedure. First, in accordance with JIS K-7122 (1987), the film for film capacitors is heated from 25°C to 350°C at a heating rate of 20°C / min (1st run), and then held in that state for 5 minutes, and then quenched at a cooling rate of 40°C / min to 25°C or less. Next, the sample after quenching is heated again from 25°C to 350°C at a heating rate of 20°C / min (2nd run), and a differential scanning calorimetry chart is obtained. Then, from the obtained differential scanning calorimetry chart, the highest midpoint glass transition temperature is obtained based on the method described in JIS K-7121 (1987), and this is the glass transition temperature of the film for film capacitors. Note that the upper limit of the temperature for the 1st and 2nd runs is set to 380°C if no glass transition temperature is observed at 350°C, and the measurement is performed again. If no glass transition temperature is observed even when the upper temperature limit is set to 380° C., it is determined that there is no glass transition temperature in the range from 25° C. to 380° C. The measurement method will be described in detail later.
[0036] The means for making the film for film capacitor of the present invention have a "melting point of 180° C. or more and 380° C. or less" and / or a "glass transition temperature of 130° C. or more and 370° C. or less" is not particularly limited, but examples thereof include a method of selecting a material that satisfies at least one of the above conditions as the raw material for resin layer B, and making the thickness of resin layer A 30% or less of the thickness of resin layer B. Another example is a method of selecting a material that satisfies at least one of the above conditions as the raw material for resin layer A and resin layer B.
[0037] In the film for film capacitor of the present invention, from the viewpoint of increasing heat resistance to a degree that allows long-term use in a high-temperature environment, the antioxidant in the resin layer A preferably contains a phenol-based antioxidant. Here, the antioxidant refers to a compound that has the effect of terminating a decomposition reaction by capturing radicals. Examples of suitable phenol-based antioxidants that capture radicals include hindered phenol-based, semi-hindered phenol-based, bisphenol-based, monophenol-based, and tetraphenol-based antioxidants. Among these phenol-based antioxidants, it is preferable to use a hindered phenol-based antioxidant from the viewpoint of reducing the deterioration of the electrodes when the film is made into a film capacitor and making it difficult to suppress the crosslinking reaction. Examples of antioxidants that can be suitably used in the resin layer A include hindered phenol-based antioxidants such as "Irganox" (registered trademark) 1010 (manufactured by BASF Japan Ltd.), "Irganox" (registered trademark) 1035 (manufactured by BASF Japan Ltd.), and "Irganox" (registered trademark) 1330 (manufactured by BASF Japan Ltd.).
[0038] From the viewpoint of maintaining performance over a long period of time, the film for film capacitors of the present invention preferably contains a carbodiimide in the resin layer A. Since film capacitors are usually used for a long period of time under high temperature and / or high humidity environments, the film for film capacitors is exposed to the risk of performance degradation due to hydrolysis of the resin layer A. By containing a carbodiimide in the resin layer A, hydrolysis of the resin constituting the resin layer A can be suppressed, and therefore the film for film capacitors can maintain its performance over a long period of time.
[0039] From the above viewpoints, the content of the carbodiimide in the resin layer A is preferably 0.01% by mass or more, and more preferably 0.04% by mass or more, when the total components of the resin layer A are taken as 100% by mass. On the other hand, from the viewpoints of suppressing a decrease in capacitance as a capacitor when used for a long period of time at high temperatures and enhancing self-healing properties, the content of the carbodiimide in the resin layer A is preferably 10% by mass or less, and more preferably 0.9% by mass or less, when the total components of the resin layer A are taken as 100% by mass.
[0040] Carbodiimides that can be suitably used for the resin layer A are not particularly limited, and examples thereof include N,N'-di-o-tolylcarbodiimide, N,N'-di-p-tolylcarbodiimide, N,N'-diphenylcarbodiimide, N,N'-di-2,6-dimethylphenylcarbodiimide, N,N'-bis(2,6-diisopropylphenyl)carbodiimide, N,N'-dioctyldecylcarbodiimide, N-triyl,N'-cyclohexylcarbodiimide, N ... Examples of the carbodiimide that can be used in the resin layer A include N,N'-di-2,2-di-tert-butylphenylcarbodiimide, N-triyl,N'-phenylcarbodiimide, N,N'-di-p-nitrophenylcarbodiimide, N,N'-di-p-aminophenylcarbodiimide, N,N'-di-p-hydroxyphenylcarbodiimide, and N,N'-di-cyclohexylcarbodiimide, as well as compounds having a carbodiimide group at the side chain or end of a polymer such as an acrylic resin. Specific examples of carbodiimides that can be used in the resin layer A include "Carbodilite" (registered trademark) (manufactured by Nisshinbo Chemical Inc.) and "Carbodista" (registered trademark) (manufactured by Teijin Limited), which are used as hydrolysis inhibitors.
[0041] The resin used in the resin layer B of the film for a film capacitor of the present invention is not particularly limited, but examples thereof include polyolefins such as polystyrene (PS), polymethylpentene (PMP), cyclic olefin (COP), and cyclic olefin copolymer (COC), polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN), polyamide 6 (PA6), polyamide 66 (PA66), polyamide 46 (PA46), and polyamide 4 polyamides such as polyamide 4T (PA4T), polyamide 6T (PA6T), modified polyamide 6T (modified PA6T), polyamide 9T (PA9T), polyamide 10T (PA10T), and polyamide 11T (PA11T); polysulfones such as polysulfone (PSU), polyethersulfone (PES), and polyphenylsulfone (PPSU); polyarylene sulfide such as polyphenylene sulfide ketone, polyphenylene sulfide sulfone, and polyphenylene sulfide ketone sulfone; Polyimides (PI) such as polyetherimide (PEI) and polyamideimide (PAI), polyaryletherketones such as polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK), and polyetherketoneetherketoneketone (PEKEKK), polytetrafluoroethylene (PTFE) (also called tetrafluoroethylene), and polytetrafluoroethylene-perfluoroalkylvinylether copolymers. Polymer (PFA) (also called tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer), tetrafluoroethylene-hexafluoropropylene copolymer (FEP) (also called tetrafluoroethylene-hexafluoropropylene copolymer), tetrafluoroethylene-ethylene copolymer (ETFE) (also called tetrafluoroethylene-ethylene copolymer), polychlorotrifluoroethylene (PCTFE) (also called trifluorochloroethylene), polyvinylidene fluoride (PVDE) (also called vinylidene fluoride).), fluorine-based polymers such as vinylidene fluoride-tetrafluoroethylene-hexafluoropyrene copolymer, polyacetal, liquid crystal polymer (LCP), polycarbonate (PC), polyarylate (PAR), phenolic resin, polyurea, melamine resin, epoxy resin, alkyd resin, mixture of syndiotactic polystyrene and polyphenylene ether, polyurethane, etc.
[0042] Among these, from the viewpoint of ensuring that at least one of the melting point and the glass transition temperature of the film for the film capacitor of the present invention falls within the above-mentioned conditions and enhancing the heat resistance in a high-temperature environment, it is more preferable to use polysulfones such as polycarbonate, polyarylene sulfide, polyethersulfone, and polyphenylsulfone, polyimide, polymethylpentene, polyetheretherketone, polyetherketoneketone, polyaryletherketone, fluorene-containing polyester, syndiotactic polystyrene, a mixture of syndiotactic polystyrene and polyphenylene ether, polyurethane, etc., either alone or in combination.
[0043] In addition, from the viewpoint of further reducing the dielectric tangent and suppressing heat generation when the film for film capacitor is used as a dielectric, the resin layer B contains at least one resin selected from the group consisting of polyarylene sulfide, polyethersulfone, polysulfone, and polyimide, and among polyimides, polyetherimide is preferred from the viewpoint of heat resistance in a high-temperature environment. And, it is more preferable that the total amount is more than 50% by mass and not more than 100% by mass when the total components of the resin layer B are taken as 100% by mass. From the above viewpoint, the total amount of the resin is more preferably 70% by mass or more, and more preferably 90% by mass or more. These resins may be homogeneous, but modified bodies, derivatives, and copolymers with other compounds may also be used. Also, they may be used alone or in a mixture of two or more types.
[0044] Polyarylene sulfide refers to a resin that contains arylene sulfide units in an amount of more than 50 mol% and not more than 100 mol% (in other words, a resin whose main constituent units are arylene sulfide units) when the total constituent units constituting the resin are taken as 100 mol%, of which a homopolymer contains no other constituent units, and a copolymer contains other constituent units in an amount of more than 0 mol% and less than 50 mol%. Other resins such as polyimide can be interpreted in the same way, except that the main constituent units change.
[0045] The film for film capacitors of the present invention may contain antioxidants, light stabilizers, ultraviolet absorbers, plasticizers, lubricants, crosslinking agents, flame retardants, antistatic agents, heat resistance improvers, colorants, slip agents, antiblocking agents, inorganic particles, resin particles, inorganic compounds, organic compounds, etc., within the scope of not impairing the properties of the film. Each of these components may be used alone or in combination of multiple types as necessary, and may be used in either the resin layer A or the resin layer B.
[0046] From the viewpoint of reducing short circuit breakdown and enhancing self-healing properties when used as a dielectric of a film capacitor, it is important that the film for a film capacitor of the present invention contains an antioxidant that satisfies at least one of the following conditions A and B. When the film for a film capacitor contains multiple antioxidants, it is interpreted that the above requirement is satisfied if at least one of the layers satisfies at least one of the conditions A and B. Condition A: The melting point is higher than 155°C and lower than 400°C. Condition B: Solid at 155°C.
[0047] The antioxidant used in the film for film capacitors of the present invention preferably has a melting point higher than 155° C., more preferably 200° C. or higher, and even more preferably 220° C. or higher, from the viewpoints of reducing thermal decomposition during long-term use in a high-temperature environment and enhancing the heat resistance of the film for film capacitors by maintaining the antioxidant function. On the other hand, from the viewpoints of suppressing a decrease in capacity as a film capacitor during long-term use at high temperatures and enhancing self-healing properties, the melting point of the antioxidant is preferably 400° C. or lower.
[0048] The melting point of the antioxidant can be measured by the following procedure. First, in accordance with JIS K-7122 (1987), the antioxidant is heated from 25°C to 400°C at a heating rate of 20°C / min to obtain a differential scanning calorimetry chart. Next, based on the method described in JIS K-7121 (1987), the melting peak temperatures are obtained from the differential scanning calorimetry chart, and the highest melting peak temperature among them is taken as the melting point. The details of the measurement method will be described later.
[0049] The antioxidant used in the film for film capacitors of the present invention is preferably solid at 155°C from the viewpoint of reducing thermal decomposition during long-term use in a high-temperature environment and improving the heat resistance of the film for film capacitors by maintaining the antioxidant function. From the above viewpoint, it is more preferable that the antioxidant satisfies the condition even at 200°C, and even more preferable that the antioxidant satisfies the condition even at 210°C. The upper limit of the temperature at which the condition is satisfied is not particularly set, but is set to 400°C in consideration of the measurable upper limit. An example of an antioxidant that does not satisfy condition A but satisfies condition B is one that does not have a melting point but exists as a solid at 155°C. Whether or not an antioxidant is solid at 155°C can be determined by measuring the melting point as described above, but in cases where there is no melting point, it can be determined visually at a temperature elevated to 155°C.
[0050] Examples of antioxidants that satisfy at least one of the above conditions A and B include "Irganox" (registered trademark) 1330 (manufactured by BASF Japan Ltd.), "Irganox" (registered trademark) 3114 (manufactured by BASF Japan Ltd.), and "ADEKA STAB" (registered trademark) AO-40 (manufactured by ADEKA Corporation).
[0051] In the film for film capacitor of the present invention, from the viewpoint of suppressing heat generation when used as a dielectric of a film capacitor and improving self-healing properties, the thickness of the resin layer A is preferably 1.0 nm or more and 1.0 μm or less. By making the thickness of the resin layer A 1.0 nm or more, the self-healing properties can be improved, and by making it 1.0 μm or less, the heat generation when used as a dielectric of a film capacitor can be reduced. From the viewpoint of self-healing properties, the thickness of the resin layer A is preferably 500 nm or less, more preferably 300 nm or less, and even more preferably 150 nm or less. From the viewpoint of reducing heat generation when used as a dielectric of a film capacitor, the thickness of the resin layer A is preferably 5.0 nm or more, more preferably 15 nm or more, and even more preferably 50 nm or more.
[0052] The thickness of the resin layer B is not particularly limited as long as it is larger than that of the resin layer A, but is preferably 0.2 μm or more and 9.0 μm or less. By making the thickness of the resin layer B 9.0 μm or less, it becomes easy to miniaturize the film capacitor when used as a film for a film capacitor. By making the thickness of the resin layer B 0.2 μm or more, it is possible to reduce the film breakage that occurs when the film for a film capacitor is processed into a film capacitor. From the viewpoint of miniaturization of the film capacitor, the thickness of the resin layer B is preferably 7.5 μm or less, more preferably 5.5 μm or less, and even more preferably 4.5 μm or less. On the other hand, from the viewpoint of reducing the film breakage during processing, the thickness of the resin layer B is preferably 1.0 μm or more, and more preferably 1.5 μm or more.
[0053] Here, the thickness of each layer can be measured by observing the cross section in the width direction-thickness direction with a field emission scanning electron microscope and using its length measuring function. The details of the measuring method will be described later.
[0054] The film for film capacitors of the present invention preferably has a thickness of 0.1 μm or more and 10.0 μm or less from the viewpoint of miniaturization of the film capacitor and reduction of film breakage during processing. From the viewpoint of miniaturization of the film capacitor, the thickness of the film for film capacitors is preferably 10.0 μm or less, more preferably 5.5 μm or less, and even more preferably 4.5 μm or less. On the other hand, from the viewpoint of reduction of film breakage during processing, the thickness of the film for film capacitors is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1.5 μm or more. Here, the thickness of the film for film capacitors can be measured using a contact type electronic micrometer. The measurement method will be described in detail later.
[0055] The metal laminate of the present invention will be described below. From the viewpoint of integration, the metal laminate of the present invention has a metal layer on at least one surface of the film for film capacitor of the present invention. In addition, for the purpose of enhancing self-healing properties, it is more preferable that the metal laminate of the present invention has a resin layer B, a resin layer A, and a metal layer in this order. Here, "having a resin layer B, a resin layer A, and a metal layer in this order" refers to a general embodiment in which the resin layer B, the resin layer A, and the metal layer are located in this order, regardless of whether there are other layers between the resin layer B and the resin layer A, between the resin layer A and the metal layer, or on the outside of the resin layer B or the metal layer.
[0056] The film for film capacitors of the present invention is preferably used as a dielectric for film capacitors, but is not limited to the type of film capacitor. Specifically, from the viewpoint of electrode configuration, it may be either a foil-wrapped capacitor or a metal-vapor-deposited film capacitor, and it is also preferably used for an oil-immersed type capacitor impregnated with insulating oil or a dry type capacitor that does not use insulating oil at all. In addition, from the viewpoint of shape, it may be a wound type or a laminated type. Among these, it is preferable to use it as a metal-vapor-deposited film capacitor including a metal laminate, due to the characteristics of the film for film capacitors of the present invention.
[0057] The metal layer can be formed by, for example, vacuum deposition, sputtering, ion plating, plating, etc. Among these methods, vacuum deposition is preferred because of its excellent productivity. When the metal layer is deposited, the oil method, tape method, etc. are used as the deposition method. The deposition pattern of the metal layer is not particularly limited, but preferred patterns include, for example, a T-margin pattern, a honeycomb pattern, and a mosaic pattern.
[0058] The metal component of the metal layer is not particularly limited, but aluminum or an alloy of aluminum and zinc is preferably used. Other metal components such as nickel, copper, gold, silver, and chromium may also be vapor-deposited simultaneously with or successively to aluminum. A protective layer may also be provided on the vapor-deposited film using oil or the like. When laminating a metal layer on a film for film capacitors consisting of a resin layer A and a resin layer B by vapor deposition, a surface treatment such as a corona discharge treatment may be performed on the vapor-deposited surface of the film for film capacitors before vapor deposition. By performing such a surface treatment, the adhesion of the vapor-deposited metal to the surface can be improved.
[0059] Next, the film capacitor of the present invention will be described. The film capacitor of the present invention uses the metal laminate of the present invention. The film capacitor of the present invention is provided with the metal laminate of the present invention, which has excellent heat resistance and self-healing properties, and thus the film capacitor of the present invention is prevented from decreasing in capacity after long-term use at high temperatures. In other words, the film capacitor can maintain its performance for a long period of time even in a high-temperature environment. The film capacitor of the present invention can be mounted in a power control unit for an automobile (for example, a power control unit for a hybrid electric vehicle, a power control unit for an electric vehicle, etc.).
[0060] The power control unit, electric vehicle, and electric aircraft of the present invention will be described below. The power control unit of the present invention has the film capacitor of the present invention. The power control unit is a system that manages power in an electric vehicle, electric aircraft, or the like that has a mechanism driven by electricity. By mounting the film capacitor of the present invention in the power control unit, it is possible to reduce the size of the power control unit itself, improve its heat resistance, and increase its efficiency, resulting in improved fuel efficiency for the electric vehicle, electric aircraft, etc.
[0061] The electric vehicle of the present invention has the power control unit of the present invention. Here, the electric vehicle refers to a vehicle having a mechanism driven by electric power, such as an electric vehicle, a hybrid vehicle, or a fuel cell vehicle. As described above, the power control unit of the present invention can be made compact and has excellent heat resistance and efficiency, so that equipping an electric vehicle with the power control unit of the present invention leads to improved fuel efficiency, etc.
[0062] The electric aircraft of the present invention has the power control unit of the present invention. Here, the electric aircraft refers to an aircraft having a mechanism driven by electric power, such as a manned electric aircraft or a drone. As described above, the power control unit of the present invention can be made compact and has excellent heat resistance and efficiency, so that equipping an electric aircraft with the power control unit of the present invention leads to improved fuel efficiency, etc.
[0063] Next, the manufacturing method of the film for film capacitor of the present invention will be described with a specific example. Note that the following example is a two-layer structure consisting of a resin layer A and a resin layer B, but the film for film capacitor of the present invention may be a two-layer structure as long as it has a resin layer A and a resin layer B, or may be a three-layer structure having other layers.
[0064] First, as a method for obtaining a sheet for the resin layer B, a method (melt film-forming method) can be used in which the raw material is fed to an extruder, melt-extruded from a slit-shaped die such as a T-die, and solidified on a cooling drum or the like to form a sheet. In addition, a method in which a solution or liquid raw material is coated on a film for solution casting substrate such as a polyolefin film, a polyethylene terephthalate film, a polyimide film, or a film obtained by silicone coating on them to enhance releasability, and then dried, polymerized, and solidified to form a sheet, or a method in which the liquid is cast on a casting belt and then dried, polymerized, and solidified to form a sheet, so-called solution film-forming method, can also be used. It is also preferable to stretch the sheet thus obtained uniaxially or biaxially. In addition, when a sheet is formed on a film for solution casting substrate, the sheet may be peeled off from the film for solution casting substrate before forming the resin layer A, but from the viewpoint of improving transportability, it is preferable to form the resin layer A without peeling.
[0065] The manufacturing method will be described in more detail below, taking as an example a film for film capacitors in which the resin layer B is a biaxially oriented polyphenylene sulfide (PPS) layer. As a raw material, PPS vacuum-dried at 170°C to 190°C is fed to an extruder, melted at 310°C to 330°C in a nitrogen atmosphere, and introduced into a T-die die. The molten resin is then extruded into a sheet from the slit of the T-die die to form a molten single-layer sheet, which is then discharged onto a casting drum whose surface temperature is kept at 10°C to 30°C, and then the sheets are brought into contact with each other by electrostatic application and cooled and solidified to obtain an unstretched PPS film.
[0066] The unstretched film obtained is stretched in the longitudinal direction at a stretching temperature of 85°C to 115°C by utilizing the difference in peripheral speed of the rolls using a longitudinal stretching machine equipped with a group of heated rolls at a stretching ratio of 2.0 to 5.0 times. Then, the widthwise both ends of the obtained uniaxially stretched film are held with clips and introduced into a tenter, where it is stretched in the widthwise direction at a stretching temperature of 95°C to 105°C by a stretching ratio of 2.5 to 5.0 times. Subsequently, it is heat-treated at 270°C to 290°C, and then subjected to a 1% to 10% relaxation treatment and cooled to room temperature. Here, the longitudinal direction refers to the running direction of the film, and the width direction refers to the direction perpendicular to the longitudinal direction in the film plane.
[0067] Then, the film surface (the side that comes into contact with the casting drum) is subjected to a current of 20 W·min / m 2 ~30W·min / m 2 After that, the film edges (width direction ends) are removed using a known slitter or the like to obtain a biaxially oriented PPS film having a thickness of 0.1 μm to 10.0 μm, which is used as the resin layer B. The thickness of the biaxially oriented PPS film can be adjusted by the slit width of the T-die die, the take-up speed of the cast drum, the stretching ratio, etc.
[0068] Examples of methods for forming resin layer A on one side of the obtained biaxially oriented PPS film include a method in which a solution or liquid resin layer A raw material is applied to resin layer B with a coater and then dried, and a method in which the resin layer A raw material is vacuum-deposited on resin layer B. When forming resin layer A by applying the raw material to one side of resin layer B, it is preferable to apply a coating composition to that side since the wettability is increased by surface treatment such as corona discharge treatment. As a result, the coating composition is prevented from being repelled, making it easier to achieve a more uniform coating thickness.
[0069] When forming the resin layer A, it is preferable to crosslink the components of the coating composition for forming the resin layer A. The crosslinking method is not particularly limited, but for example, a method of using a composition having a plurality of reactive sites as a coating composition for forming the resin layer A and crosslinking them with heat, ultraviolet light, electron beams, etc. can be mentioned. Examples of compositions having a plurality of reactive sites include acrylates or urethane acrylates having two or more vinyl groups, epoxies having two or more epoxy groups, condensates of melamine and formaldehyde, mixtures of compounds having two or more isocyanate groups and compounds having three or more hydroxyl groups, mixtures of compounds having two or more isocyanate groups and compounds having three or more amino groups, etc. Among these, from the viewpoint of promoting the decomposition of the resin layer A at the time of insulation breakdown and enhancing the self-healing property, it is preferable to use acrylates or urethane acrylates having two or more vinyl groups, mixtures of compounds having two or more isocyanate groups and compounds having three or more hydroxyl groups, and mixtures of compounds having two or more isocyanate groups and compounds having three or more amino groups.
[0070] In order to promote the crosslinking reaction, when forming the resin layer A, a catalyst such as an acid or a base, or an additive such as a cationic initiator, an anionic initiator, or a radical initiator may be added according to the reactivity of the reaction points. For example, when an acrylate having two or more vinyl groups is used as a coating composition for forming the resin layer A, a coating liquid containing a radical initiator that generates radicals by ultraviolet light is prepared, and the coating liquid is applied to a biaxially oriented PPS film, and then the crosslinking reaction can be promoted by irradiating the film with ultraviolet light. The radical initiator is not particularly limited, but a hydroxyalkylphenone type initiator, an aminoacetophenone type initiator, or the like that generates radicals by ultraviolet light can be used. A specific example is "Omnirad" (registered trademark) 184, which is a hydroxyalkylphenone type initiator. By forming a crosslinked structure in the resin layer A in this way, it becomes easy to increase the heat resistance of the film for film capacitor of the present invention.
[0071] As an example, a method of forming the resin layer A by using a bar coater will be described. First, a coating liquid is prepared by mixing 100 parts by mass of acrylate, 1 to 5 parts by mass of α-hydroxyalkylphenone as a photopolymerization initiator, and 800 to 1000 parts by mass of 2-butanone. The prepared coating liquid is applied to the corona discharge-treated surface of the biaxially oriented PPS film by a bar coater so that the coating thickness after curing is 50 to 500 nm. This is introduced into a drying furnace at 80°C to 100°C and dried for 30 seconds to 2 minutes. Next, the dried biaxially oriented PPS film is introduced into a UV irradiation device and exposed to an illuminance of 40 mW / cm. 2 ~70mW / cm 2 , irradiation amount 0.05J / cm 2 ~0.3J / cm 2 The coating is then cured by irradiating it with UV light under conditions of an oxygen concentration of 90 ppm to 300 ppm to form a resin layer A (at this time, the biaxially oriented PPS film becomes a resin layer B). In this way, a film for a film capacitor can be obtained.
[0072] A metal film such as aluminum or an alloy of aluminum and zinc can be laminated on the obtained film for film capacitors by vacuum deposition, sputtering, ion plating, plating or the like to obtain the metal laminate of the present invention. EXAMPLES
[0073] The film for a film capacitor of the present invention will be specifically described below using examples. The methods for measuring the property values and the methods for evaluating the effects are as follows.
[0074] (1) Thickness of film for film capacitor The thickness of ten randomly selected points of the film for film capacitors was measured in an atmosphere of 23°C and 65% RH using a contact-type electronic micrometer (K-312A type) manufactured by Anritsu Corp. The arithmetic mean value of the thicknesses at the ten points was regarded as the thickness of the film for film capacitors.
[0075] (2) Thickness of resin layer A, thickness of resin layer B Using a microtome method, an ultra-thin section of the film for film capacitors with a width of 5 mm was prepared having a cross section in the width direction-thickness direction, and the cross section was platinum-coated to prepare an observation sample. Next, the cross section was observed at an accelerating voltage of 1.0 kV using a Hitachi field emission scanning electron microscope (S-4800), and the thickness of each layer was measured from any point in the observed image. The observation magnification was 10,000 times, and the thicker layer of the two layers was designated as resin layer B, and the thinner layer was designated as resin layer A. Furthermore, similar measurements were performed a total of 20 times, and the average values of the thickness of the thinner layer and the thickness of the thicker layer were designated as the thickness of resin layer A and the thickness of resin layer B of the film for film capacitors, respectively.
[0076] (3) Melting point of film for film capacitor According to JIS K-7122 (1987), 3.0 mg of the film for film capacitors was weighed as a sample, and the sample was heated at a heating rate of 20 ° C / min from 25 ° C to Tmax ( ° C) at a heating rate of 20 ° C / min using a differential scanning calorimeter (SEIKO INSTRUMENTS EXSTAR DSC6220) to obtain a differential scanning calorimeter chart. From the obtained differential scanning calorimeter chart, the melting peak temperature was obtained based on the method described in JIS K-7121 (1987). The highest melting peak temperature among the obtained melting peak temperatures was taken as the melting point of the film for film capacitors. Tmax ( ° C) was first set to 350 ° C and measurement was performed, and if no melting point was observed, it was set to 380 ° C and measurement was performed again. If no melting point was observed at Tmax = 380 ° C, it was considered that there was no melting point in the measurement range.
[0077] (4) Glass transition temperature of film for film capacitor According to JIS K-7122 (1987), 3.0 mg of the film for film capacitors was weighed as a sample, and the sample was heated from 25 ° C. to Tmax (° C.) at a heating rate of 20 ° C. / min using a differential scanning calorimeter (Seiko Instruments EXSTAR DSC6220) at a heating rate of 20 ° C. / min (1st run), and then held in that state for 5 minutes, and then rapidly cooled to 25 ° C. or less at a cooling rate of 40 ° C. / min. Then, the temperature was raised again from 25 ° C. to Tmax (° C.) at a heating rate of 20 ° C. / min (2nd run), and a differential scanning calorimeter chart of the 2nd run was obtained. From the differential scanning calorimeter chart of the 2nd run, the intermediate glass transition temperature was determined based on the method described in JIS K-7121 (1987), and the highest intermediate glass transition temperature among them was taken as the glass transition temperature of the film for film capacitors. Tmax (°C) was first set to 350°C and measurements were performed, and if no glass transition temperature was observed, it was set to 380°C and measurements were performed again. If no glass transition temperature was observed at Tmax = 380°C, it was considered that there was no glass transition temperature in the measurement range.
[0078] (5) Soluble content of resin layer A in each solvent 0.10 g of a sample scraped off from the resin layer A of the film for film capacitors was put into 1.00 g of a specified solvent, and then mixed for 10 minutes with a vortex mixer (VTX-3000L, manufactured by AS ONE Corporation). The solution was then filtered through a filter (090045MFPVDF, pore size 0.45 μm, manufactured by Taiyo Co., Ltd.) and the extracted filtrate was dried in an oven at 110 ° C for 1 hour, and the mass (g) after drying was measured. The soluble content in the solvent was calculated using the following formula, and the average value of n = 3 times was taken as the soluble content in the solvent of the resin layer A of the film for film capacitors. (Formula) Soluble in solvent (%) = mass after drying (g) × 100 / 1.00 (g).
[0079] (6) Long-term life test (film capacitor characteristics) The surface of the resin layer A of the film for film capacitors is the α surface, and the α surface is subjected to a load of 25 W·min / m 2A corona discharge treatment was performed in the atmosphere with a treatment intensity of 10 ... 0h Next, a voltage of 500 VDC was applied to the film capacitor element in a 165°C environment, and after 100 hours, it was taken out and the capacitance was measured in the same way. 100h C 0h and C. 100h The capacity retention rate after 100 hours was calculated using the following formula. The same measurement was performed on each of the five elements, and the average value was used as the capacity loss rate after 100 hours of the film capacitor element. The film capacitor characteristics were evaluated based on the capacity retention rate after 100 hours using the following evaluation criteria. <Calculation formula> Capacity retention rate (%)=100×C 100h / C 0h <Evaluation criteria> The evaluation results were ranked in order of S to D, indicating that the film capacitor properties were excellent, with S to C being pass marks and D being fail marks, as it was practically difficult to use the film as a capacitor film. S: The capacity retention rate after 100 hours was 95% or more. A: The capacity retention rate after 100 hours was 70% or more and less than 95%. B: The capacity retention rate after 100 hours was 50% or more and less than 70%. C: The capacity retention rate after 100 hours was 20% or more and less than 50%. D: The capacity retention rate after 100 hours was less than 20%.
[0080] (7) Self-healing (SH) The surface of the resin layer A of the film for film capacitors is the α surface, and the α surface is subjected to a load of 25 W·min / m 2 The corona discharge treatment was then performed in the atmosphere at a treatment intensity of 1.0×10. The corona discharge treatment surface was then subjected to a bell jar type vacuum deposition apparatus at a pressure of 1.0×10. -3 Aluminum was evaporated at 20 Pa and a filament voltage of 2.6 kV to form a 50 nm evaporated film to obtain a metal laminate. Next, the obtained metal laminate was attached to an A4 size aluminum frame, placed in an oven kept at 150 ° C., and heated for 100 h. Thereafter, the metal laminate was removed from the oven and cut into a 12 cm x 7.5 cm rectangular shape with the long side in the longitudinal direction to obtain a test piece. Next, a 10 cm square 1 mm thick "Teflon" (registered trademark) sheet was placed on a 1 m x 2 m copper plate, and the test piece was placed so that the short side of the test piece and one side of the "Teflon" (registered trademark) sheet were parallel, and the entire area of 1 cm from the short side of one side of the test piece was placed on the "Teflon" (registered trademark) sheet. Then, the part of the test piece that was on the "Teflon" (registered trademark) sheet was cut by 2 cm. 2A conductive rubber electrode in the shape of a 5 cm square plate was placed on the "Teflon" (registered trademark) sheet so that it was sandwiched between the rubber electrode, the test piece, and the "Teflon" (registered trademark) sheet. In addition, a cylindrical electrode with a diameter of 3 cm was placed on the rubber electrode so that the center of gravity was located above the area where the rubber electrode, the test piece, and the "Teflon" (registered trademark) sheet overlapped. Then, a DC power source was connected to the cylindrical electrode and the copper plate via an electric wire, and a voltage of 100 VDC was applied as an initial voltage. After 15 seconds at this voltage, the applied voltage was gradually increased in a stepwise manner to the initial voltage of +800 VDC at 100 VDC / 30 seconds. This so-called step-up test was repeated to generate multiple insulation breakdown marks on the metal layer laminated film. The generated insulation breakdown marks were visually observed, and the insulation breakdown marks where two or more insulation breakdown marks overlapped were regarded as one SH defective area, and the insulation breakdown marks where they did not overlap were regarded as one normal area. The number of each was calculated, and the SH defect rate was calculated using the following formula. The same measurement was performed twice, and the average value was adopted as the SH defect rate of the film. If no breakdown occurred, the same measurement was performed with an initial voltage of 900 VDC. If no breakdown occurred at 900 VDC, the initial voltage was changed to +800 VDC and the same measurement was performed until breakdown occurred. If no breakdown occurred even with an initial voltage of 10,000 VDC, the SH failure rate was recorded as 0%. Based on the SH failure rate of the film, the self-healing property was evaluated according to the following criteria. <Calculation formula> SH defect rate (%) = 100 x (number of SH defective parts) / (number of normal parts + number of SH defective parts) <Evaluation criteria> The evaluation results were ranked in order of S to D, indicating the degree of self-healing ability, with S to C being pass, and D being fail because it was practically difficult to use as a capacitor film. S: The SH defect rate was between 0% and 6%. A: The SH defect rate was greater than 6% and less than 10%. B: The SH defect rate was greater than 10% and less than 16%. C: The SH defect rate was greater than 16% and less than or equal to 25%. D: The SH defect rate was greater than 25%.
[0081] (8) Heat shrinkage rate at 150℃ The heat shrinkage was measured using the following equipment and conditions. ·Length measurement device: Universal projector Sample size: Length 150mm (width direction) x width 10mm (length direction) Heat treatment equipment: Gear oven Heat treatment conditions: 150℃, 30 minutes ·Load: 3g ·Calculation method Before heat treatment, a sample of the above-mentioned size was taken from the film for film capacitors, and marks were drawn on the sample at intervals of 100 mm. The distance between the marks after heat treatment was then measured, and the heat shrinkage was calculated using the following formula. The same measurement was performed five times, and the average of the obtained heat shrinkage was taken as the 150°C heat shrinkage (%) of the film for film capacitors. Heat shrinkage rate (%) = {(gauge length before heat treatment) - (gauge length after heat treatment)} x 100 / gauge length before heat treatment. Good: Thermal shrinkage at 150°C was 2.0% or less. ×: Thermal shrinkage at 150° C. was more than 2.0%.
[0082] (9) Melting point of antioxidant According to JIS K-7122 (1987), 3.0 mg of antioxidant was weighed as a sample, and the sample was heated from 25°C to Tmax (°C) at a temperature increase rate of 20°C / min using a differential scanning calorimeter (EXSTAR DSC6220 manufactured by Seiko Instruments) to obtain a differential scanning calorimeter chart. From the obtained differential scanning calorimeter chart, the melting peak temperature was determined based on the method described in JIS K-7121 (1987). The highest melting peak temperature among the obtained melting peak temperatures was determined as the melting point of the antioxidant. In addition, the observation upper limit Tmax (°C) was set to 400°C during the measurement, and when no melting point was observed, it was considered that the antioxidant did not have a melting point within the measurement range.
[0083] [Raw materials, films] The raw materials and films used in the production of the film for film capacitors are as follows.
[0084] <Raw material for resin layer A> [resin] Urethane acrylate 1: Product name "UV-3500BA", difunctional urethane acrylate diluted with butyl acetate, manufactured by Mitsubishi Chemical Corporation Urethane acrylate 2: Product name "UN-3320HA", 6-functional urethane acrylate, manufactured by Negami Chemical Industries, Ltd. Polyurethane 1: Aqueous dispersion of aromatic polyester polyurethane produced by the following procedure. (Manufacturing Procedure) A polyester polyol was obtained from 665 parts by mass of terephthalic acid, 635 parts by mass of isophthalic acid, 460 parts by mass of 1,4-butanediol, and 470 parts by mass of neopentyl glycol as starting materials, to which 320 parts by mass of adipic acid and 270 parts by mass of dimethylolpropionic acid were added to obtain a carboxyl group-containing polyester polyol. 160 parts by mass of tolylene diisocyanate was added to 1900 parts by mass of this polyester polyol to obtain an aromatic polyester polyurethane solution. The obtained solution was poured into an aqueous ammonia solution to remove the solvent, and an aromatic polyester polyurethane water dispersion was obtained.
[0085] [Ingredients other than resin] Oxazoline 1: "Epocross" (registered trademark) K2030E, manufactured by Nippon Shokubai Co., Ltd. 2-Butanone: Fujifilm Wako Pure Chemical Industries, Ltd. Photopolymerization initiator: “Omnirad” (registered trademark) 184 manufactured by IGM Resins BV, 1-hydroxycyclohexyl phenyl ketone Antioxidant 1: Trade name "Irganox" (registered trademark) 1010, hindered phenol-based antioxidant, manufactured by BASF Japan Ltd., melting point 110°C, melts at 155°C Antioxidant 2: Trade name "Irganox" (registered trademark) 245, triethylene glycol bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], hindered phenol-based antioxidant, manufactured by BASF Japan Ltd., melting point 76°C, melting at 155°C Antioxidant 3: Trade name "ADEKA STAB" (registered trademark) AO-40, 4,4'-Butylidenebis (6-tert-butyl-m-cresol), phenol-based antioxidant, manufactured by ADEKA Corporation, melting point 214°C, solid at 155°C Antioxidant 4: Trade name "Irganox" (registered trademark) 1330, hindered phenol-based antioxidant, manufactured by BASF Japan Ltd., melting point 240°C, solid at 155°C Carbodiimide 1: Trade name "Carbodilite" (registered trademark) carbodiimide, hydrolysis inhibitor, manufactured by Nisshinbo Chemical Inc.
[0086] <Raw materials and films used in producing resin layer B> Polyphenylene sulfide resin granules 1 (PPS granules 1): In a 1-liter autoclave equipped with a process stirrer, 1.00 mol of 48% by mass sodium hydrosulfide, 1.02 mol of 95% by mass sodium hydroxide, 1.54 mol of N-methyl-2-pyrrolidone (NMP), 0.47 mol of sodium acetate, and 140 g of ion-exchanged water were charged, and while stirring at 250 rpm, nitrogen was passed through at normal pressure and gradually heated to 228°C over about 3 hours, and 212 g of water and 4 g of NMP were distilled, and the reaction vessel was cooled to 160°C. Next, 1.00 mol of p-dichlorobenzene (p-DCB) and 1.32 mol of NMP were added, and the reaction vessel was sealed under nitrogen gas. Then, while stirring at 250 rpm, the temperature was raised from 200°C to 235°C at a rate of 0.7°C / min, and after reaching 235°C, the reaction was continued at 235°C for 95 minutes. Then, the temperature was raised to 270°C at a rate of 0.8°C / min and held for 100 minutes. After reaching 270°C, 1 mole of water was injected into the system over 15 minutes. After holding at 270°C for 100 minutes, it was cooled to 200°C at a rate of 1.0°C / min, and then cooled to near room temperature by applying room temperature cooling water to the autoclave. Next, the contents were taken out, diluted with 0.4 liters of NMP, stirred at 85°C for 30 minutes, and then the solvent and solids were filtered off with a sieve (80 mesh). Furthermore, 0.5 liters of NMP was added to the obtained solid, stirred at 85°C for 30 minutes, and the solids were filtered off. Then, the obtained solids were washed three times with 0.9 liters of warm water and filtered off. The particles (solids) thus obtained were washed twice with 1 liter of warm water and filtered off to obtain polymer particles. This was dried with hot air at 80° C. and then dried under reduced pressure at 120° C. to obtain polyphenylene sulfide (PPS) resin granules (PPS granules 1) having a melting point of 280° C. and a weight average molecular weight of 70,000.
[0087] PPS raw material for film 1 (PPS1): 100 parts by mass of PPS granules 1, 0.05 parts by mass of calcium carbonate particles 1 ("NITOREX" #30PS, manufactured by Nitto Funka Kogyo Co., Ltd.) with an average particle size of 0.7 μm, and 0.2 parts by mass of calcium stearate were mixed and pelletized to prepare a resin pellet mainly composed of PPS. The resin pellets obtained were fed into a vented co-rotating twin-screw kneading extruder (manufactured by Japan Steel Works, Ltd., screw diameter 30 mm, screw length / screw diameter = 45.5) heated to 320 ° C, melt extruded at a residence time of 90 seconds and a screw rotation speed of 150 rpm, discharged in the form of a strand, and cooled with water at a temperature of 25 ° C. Then, they were immediately cut to prepare chips, which were used as PPS raw material 1 for film (PPS1).
[0088] PPS film 1: PPS1 was vacuum dried at 180°C for 3 hours, fed to an extruder, melted at 320°C under a nitrogen atmosphere, and introduced into a T-die die. Then, from the T-die die, it was extruded into a sheet to form a molten monolayer sheet, which was discharged onto a casting drum with a surface temperature of 25°C and a rotation speed of 4.0 m / min, and cast by cooling and solidifying it by contacting it with an electrostatic application method to obtain an unstretched film. Then, using a longitudinal stretching machine equipped with a group of heated rolls, the unstretched film was stretched at a stretching temperature of 103°C at a ratio of 3.2 times in the longitudinal direction by utilizing the difference in the peripheral speed of the rolls. The uniaxially stretched film thus obtained was supported by clips at both ends in the width direction and introduced into a tenter, where it was stretched at a stretching temperature of 102°C at a ratio of 3.4 times in the width direction. It was then heat-treated at 280°C, followed by a 2% relaxation treatment and cooled to room temperature. Then, the film surface (the side contacting the cast drum) was stretched at 25 W·min / m 2 After that, the film edges were removed to obtain a biaxially oriented PPS film having a thickness of 4.3 μm.
[0089] Example 1 According to the coating formulation in Table 1, 100 g of a coating liquid was prepared by mixing urethane acrylate 1, 2-butanone, antioxidant 1, and photopolymerization initiator in a ratio of 100:900:0.05:0.3 (mass ratio). As shown in Table 1, PPS film 1 was used as the base film (resin layer B), and the coating liquid was uniformly applied to the corona-treated surface of the PPS film 1 using a bar coater so that the thickness after curing would be the thickness (100 nm) of resin layer A shown in Table 1, and then dried in a drying oven at 90° C. for 1 minute. This was then introduced into a UV irradiation device and dried at an illuminance of 50 mW / cm. 2 , irradiation amount 0.1J / cm 2 The coating was cured under conditions of an oxygen concentration of 100 ppm to form resin layer A, and then the laminate of resin layer A and resin layer B was wound up to obtain a film for film capacitors. The evaluation results are shown in Table 1.
[0090] (Examples 2 to 7, Comparative Examples 3 to 4) A film for a fill capacitor was obtained in the same manner as in Example 1, except that the coating liquid formulation and the thickness of the resin layer A were as shown in Tables 1 and 2. The evaluation results are shown in Tables 1 and 2.
[0091] Comparative Example 1 100 parts by mass of dimethyl terephthalate, 60 parts by mass of ethylene glycol, and 0.09 parts by mass of calcium acetate monohydrate were placed in a reactor, and the temperature was raised while heating and distilling off methanol to carry out an ester exchange reaction. The temperature was raised to 230°C over 4 hours from the start of the reaction, and the ester exchange reaction was essentially completed. Next, 0.3 parts by mass of silica particles having a particle size of 1.2 μm were added as an ethylene glycol slurry. After the addition of the slurry, 0.06 parts by mass of phosphoric acid and 0.04 parts by mass of antimony trioxide were further added, and the reaction system was gradually decompressed, the temperature was raised, and the polycondensation reaction was carried out for 4 hours. In this way, polyethylene terephthalate with an intrinsic viscosity of 0.66 was obtained. The obtained polyethylene terephthalate was dried by a conventional method, fed to an extruder, melted at 290°C, and discharged into a sheet, and the molten sheet-like material was quenched on a cooling roll by an electrostatic application adhesion method to form a non-oriented sheet. The obtained non-oriented sheet was stretched 3.8 times in the longitudinal direction at 80°C by a roll stretching method to form a uniaxially stretched film. Next, a coating solution was applied to both sides of the obtained uniaxially stretched film, in which 10 parts by mass of "Epocross" (registered trademark) K2020E manufactured by Nippon Shokubai Co., Ltd. was added as an oxazoline compound to the above-mentioned polyurethane in terms of solid content concentration, and the uniaxially stretched film after coating was introduced into a tenter and stretched 4.1 times in the width direction at 110°C. Thereafter, a heat treatment was performed at 230°C while further relaxing by 8% in the width direction. In this way, a biaxially oriented polyester film with a thickness of 5.0 μm was obtained. The thickness of the coating layer was adjusted by the solid content concentration, and the thickness of the base polyester film (sometimes referred to as PET film 1) was adjusted by the discharge amount of the extruder (same as in Comparative Example 2).
[0092] Comparative Example 2 A non-oriented sheet was obtained in the same manner as in Comparative Example 1, and then stretched 4.2 times in the machine direction at 90°C to obtain a uniaxially stretched film. Then, antioxidant 2 was added to polyurethane so that the concentration was 0.5% by mass, and a coating liquid prepared using water as a medium was applied to both sides of the uniaxially stretched film. Next, the uniaxially stretched film to which the coating liquid was applied was stretched 3.9 times in the width direction at 110°C. Heat treatment was performed at 230°C to obtain a biaxially stretched polyester film with a coating layer thickness of 0.055 μm and a substrate polyester film (sometimes referred to as PET film 2) thickness of 6.0 μm. The evaluation results are shown in Table 2.
[0093] [Table 1]
[0094] [Table 2] [Industrial Applicability]
[0095] The film for film capacitors of the present invention can be used for various applications such as packaging applications, tape applications, cable wrapping, and electrical applications including film capacitors, and can be particularly suitably used for high-voltage film capacitor applications that require high voltage resistance and reliability at high temperatures.
Claims
1. A film for a film capacitor having two types of resin layers with different thicknesses, A film for a film capacitor, in which, of the two types of resin layers, the layer having a relatively smaller thickness is resin layer A and the layer having a relatively larger thickness is resin layer B, the film has the resin layer A on at least one side of the resin layer B, and satisfies both of the following conditions 1 and 2. Condition 1: When the total amount of all the components of the resin layer A is taken as 100% by mass, the resin layer A contains an antioxidant in an amount of 0.01% by mass or more and 10% by mass or less. Condition 2: When the total amount of all the components of the resin layer A is taken as 100% by mass, the amount of the soluble portion of the resin layer A in any one of the following solvents a) to c) is 30% by mass or less. a) Methyl ethyl ketone b) Toluene c) Dioxane
2. 2. The film for a film capacitor according to claim 1, having a melting point measured by DSC of 180° C. or more and 380° C. or less, and / or a glass transition temperature measured by DSC of 130° C. or more and 370° C. or less.
3. The film for a film capacitor according to claim 1 or 2, wherein the antioxidant comprises a phenol-based antioxidant.
4. The film for a film capacitor according to claim 1 or 2, wherein the resin layer A contains a carbodiimide.
5. The film for a film capacitor according to claim 4, wherein the content of the carbodiimide in the resin layer A is 0.01% by mass or more and 10% by mass or less when all components of the resin layer A are taken as 100% by mass.
6. 3. The film for a film capacitor according to claim 1, wherein the resin layer A has at least one structure selected from the group consisting of an ester bond, an ether bond, a carbonate bond, a urethane bond, a urea bond, an amide bond, an imide bond, an oxazoline ring, and an alkylene group.
7. 3. The film for film capacitors according to claim 1 or 2, wherein the resin layer A has a unit structure of at least one polymer selected from the group consisting of urethane acrylate polymers, acrylate polymers, urethane methacrylate polymers, methacrylate polymers, aliphatic polyethers, aliphatic polyesters, aliphatic polyamides, polyurethanes, polyureas, and epoxy resins.
8. 3. The film for a film capacitor according to claim 1 or 2, wherein the resin layer B contains at least one of the group consisting of polyarylene sulfide, polyethersulfone, polysulfone, polyimide, polyetheretherketone, and polyetherimide, and the total amount thereof is more than 50 mass% and 100 mass% or less.
9. The film for a film capacitor according to claim 1 or 2, containing an antioxidant that satisfies at least one of the following conditions A and B: Condition A: The melting point is higher than 155° C. and equal to or lower than 400° C. Condition B: Solid at 155°C.
10. The film for a film capacitor according to claim 1 or 2, wherein the resin layer A has a thickness of 1.0 nm or more and 1.0 μm or less.
11. The film for a film capacitor according to claim 1 or 2, having a thickness of 0.1 μm or more and 10.0 μm or less.
12. A metal laminate comprising the film for a film capacitor according to claim 1 or 2 and a metal layer on at least one surface of the film.
13. The metal laminate according to claim 12 , comprising the resin layer B, the resin layer A, and the metal layer in this order.
14. A film capacitor comprising the metal laminate according to claim 13.
15. A power control unit comprising the film capacitor according to claim 14.
16. An electric vehicle comprising the power control unit according to claim 15.
17. An electric aircraft comprising the power control unit according to claim 15.
Citation Information
Patent Citations
Polyester film for capacitor
JP1997141809A